Analisis Potensi Miskonsepsi Dalam Penyajian Materi Pertidaksamaan Linier Satu Variabel Pada Buku Teks Matematika SMP - Nabila Azuhra; Muhammad Rasyid Mondol; Aulia Syahputri; Christania Rossalin Sagala; Nurul Sakinah; Wingston Leonard Sihombing (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
junior high school level. However, in practice, it often leads to misconceptions among students. One of the main contributing factors is the way the material is presented in textbooks, which serve as the primary reference for both teachers and students. This study aims to analyze the potential misconceptions found in two mathematics textbooks, namely Matematika SMP/MTs Kelas VII Semester 1 published by BS Press (2017) and Persamaan dan Pertidaksamaan Linear Satu Variabel written by Winie Ananda (2022). This research employed a descriptive qualitative approach using content analysis. The instrument focused on three aspects: (1) the rule of reversing inequality signs when multiplying or dividing by negative numbers, (2) the conceptual differences between linear equations in one variable (PLSV) and linear inequalities in one variable (PtLSV), and (3) the representation of solution sets on the number line. Thefindings indicate that both textbooks still contain potential sources of misconceptions. The use of the term “root of PtLSV” is conceptually inaccurate, the rule of sign reversal is presented only procedurally, the distinction between PLSV and PtLSV is insufficiently emphasized, and the graphical representation on the number line is not adequately explained. These results highlight the need to improve the presentation of PtLSV materials in textbooks and encourage teachers to provide stronger conceptual explanations to foster meaningful learning.